The Keys to Usability in e-Learning Websites - Kukulska-Hulme, Agnes; Shield, Lesley (Proceedings of the International Conference on Networked Learning, 2004)
Technical knowledge is insufficient when designing and testing websites for e-learning. At the Open University, usability has been at the heart of a project aimed at enabling academic course developers to participate on an equal footing with other professionals in addressing website usability. Our investigations have included interviews with key staff, a review of usability literature, case studies, usability tools, workshops, an investigation of student and tutor experiences, and an analysis of student ratings for websites. We outline our concept of ‘pedagogical usability’, a set of key cosiderations for improving the experience of web-based learning.